Estudo de um Controlador Fuzzy aplicado a um sistema eólico de velocidade variável conectado à rede elétrica - Rocha, Manassés Medeiros (Brasil, 2017)
Wind energy is a renewable source that has grown in application and technological development. Moreover, the generation of electricity from these systems does not compromise the environment as traditional systems such as the hydraulic and thermal generation of electricity. Responsible for capturing and converting wind energy into electricity, the wind turbine is the main component of wind power generation systems. Due to the nonlinear wind behavior, the development of a mathematical model that describes the behavior of such a system is a complex and sometimes impractical task. However, some applications involving modern controls systems can be used with the aim of optimizing the use of wind. One possibility is the use of a control system based on Fuzzy Logic, since this technique does not require the mathematical detailing of the system. Thus, this work aims to analyze the behavior of a Fuzzy Controller applied to a variable-speed wind turbine with permanent magnet synchronous generator (PMSG) connected to the grid. The main focus was the use of the system to simulate a real load composed by the network to flow the generated energy. The performance of the Fuzzy Controller was verified when compared to that of a Classical Proportional Controller. The results show that the Fuzzy Control presents a higher efficiency and increases the capacity of power generation with reduction in the time of accommodation and less error in permanent regime
Keywords: Energia eólica; Fonte renovável; Lógica Fuzzy; PMSG; Wind energy; Renewable source; Fuzzy logic; PMSG; ENGENHARIAS::ENGENHARIA ELETRICA